The impact of long-term antiseizure treatment on cognitive decline in late-onset epileptic prodromal Alzheimer's disease: an exploratory study. - Cretin, Benjamin; Philippi, Nathalie; Bousiges, Olivier; Dibitonto, Laure; Blanc, Frederic (Frontiers in Aging Neuroscience, 2026)
Background: The well-documented bidirectional relationship between Alzheimer's disease (AD) and epilepsy suggests that seizures are not merely a complication of AD but may also contribute to disease progression. Emerging evidence indicates that antiseizure medications (ASMs) could potentially slow the disease course and act as disease-modifying agents if initiated early. Objectives: We investigated the long-term cognitive and functional effects of ASMs when introduced at the prodromal stage of AD. Methods: Twenty-two sporadic epileptic prodromal AD patients (epADs) and 21 matched subjects without epilepsy (nepADs) were followed for a median of 7 years. Baseline cognition, daily functioning, clinical/paraclinical features, and pharmacological profiles were compared. Annual assessments included cognition, pharmacological burden, and functional impairment. Results: At the final follow-up, epADs evidenced more preserved cognition than nepADs, reflecting a significantly slower annual rate of cognitive decline (−1.2 ± 0.9 vs. −2.7 ± 2.4 points/year on the MMSE score, respectively; p = 0.01). They were also less likely to require neuroleptics (9.1% vs. 47.6%, p < 0.01) or memantine (0% vs. 28.6%, p < 0.01). However, epADs and nepADs had the same proportion of Alzheimer's dementia at the final follow-up visit (90.9% vs. 90.5%, p = 0.96). Despite being significant, these results had low statistical power due to our small sample size and should be considered exploratory. Conclusion: Our findings support the idea that early ASM treatment may attenuate cognitive decline in sporadic prodromal AD patients with comorbid epilepsy. However, these benefits were not accompanied by a lower dementia rate at the final follow-up visit, suggesting that ASMs alone are insufficient for sustained disease modification. Combinatorial therapeutic strategies may be needed to achieve long-term neuroprotection in AD.